O futuro da auditoria e o impacto na gestão do risco empresarial das PME - Pacheco, Inês Filipa Gonçalves (2021)
Organizations have been faced with several technological evolutions, contributing to increased competitiveness between companies, where the most effective and efficient companies lead. In this way, it is intended to understand how companies deal with the management of business risks and whether companies are aware of technological developments and all the changes that may occur there, namely how auditing can evolve to create value for the organizations. This investigation aims to verify the value that organizations attribute to internal and external auditing, whether organizations have business risk management, how they deal with risks, how technological evolution may impact information systems and whether auditing should change the its paradigm in order to create value for entities. The qualitative methodology was selected for the investigation. Data collection was carried out using questionnaires and interviews. As the Portuguese business fabric is essentially made up of small and medium-sized companies and, as they are more sensitive to technological changes and less valued auditing and business risk management, this research had small and medium-sized companies from Paredes as its population, Penafiel and Paços de Ferreira. The questionnaire was answered by 63 companies and 3 interviews were conducted with statutory auditors. It was concluded that the majority of small and medium-sized companies in the study population despise auditing and business risk management. The success of these companies comes from their vast business knowledge, as they are mostly family businesses, with a few generations. The added value that these companies attribute to the audit is the fact that the auditor advises management on business risks. Thus, if auditing changes its paradigm to continuous, as a result of technological developments, these companies will be better prepared for the volatility of risks that may occur.